Efektivitas Pembelajaran Tatap Muka (PTM) di New Normal Terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Kewarganegaraan - Muhammad Nasrul Waton (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
Education is a process of individual self-development of one's personality that is carried out consciously and responsibly to be able to improve knowledge, skills and attitudes as well as values ??so that they are able to adapt themselves with the environment. Many things change when re-learning is done with a face-to-face learning system (PTM) after three semesters of learning with an online system. A person will reap the results of his learning when he is interested in something he is learning. The research method used in this study is a quantitative approach to determine how much effectiveness learning in the new normal era has on the learning outcomes of class XI IPS 1 Madrasah Aliyah Darul Ma'arif Kedamean students on March 2021. To explain how the level of effectiveness of learning in the new normal era, the author uses the SPSS 16 for windows application as a tool to find out the results of the research. from the results of the study obtained data that explains how the effectiveness of learning in the new normal era is 73.5% with an interpretation that has a fairly high category. so that face-to-face learning in the new normal era can be said effectively implemented at Madrasah Aliyah Darul Ma'arif Miru Kedamean Gresik